Circular RNA Protein Tyrosine Kinase 2 Promotes Cell Proliferation, Migration and Suppresses Apoptosis via Activating MicroRNA-638 Mediated MEK/ERK, WNT/β-Catenin Signaling Pathways in Multiple Myeloma - Zhou, Fan; Wang, Dongjiao; Zhou, Nian; Chen, Haimin; Shi, Haotian; Peng, Rong; Wei, Wei; Wu, Lixia (Frontiers in Oncology, 2021)
Our previous study observed that circular RNA protein tyrosine kinase 2 (circ-PTK2) was upregulated and correlated with worse clinical features and unfavorable prognosis in multiple myeloma (MM) patients. Thus, this study aimed to further characterize the regulatory function of circ-PTK2 on cell malignant activities and its target microRNA-638 (miR-638) as well as downstream MEK/ERK, WNT/β-catenin signaling pathways in MM. The effect of circ-PTK2 on MM cell proliferation, apoptosis, migration, invasion and its potential target miRNAs was assessed by transfecting circ-PTK2 overexpression plasmids into U226 cells and circ-PTK2 knock-down plasmids into LP-1 cells. Furthermore, the interaction between circ-PTK2 and miR-638 mediated MEK/ERK and WNT/β-catenin signaling pathways was validated by rescue experiments. Circ-PTK2 was overexpressed in most MM cell lines compared to normal plasma cells. Overexpressing circ-PTK2 promoted proliferation and migration, inhibited apoptosis in U266 cells, but did not affect cell invasion; knocking down circ-PTK2 achieved opposite effect in LP-1 cells. Besides, circ-PTK2 reversely regulated miR-638 expression but not miR-4690, miR-6724, miR-6749 or miR-6775. The following luciferase reporter assay illustrated the direct bind of circ-PTK2 towards miR-638. In rescue experiments, overexpressing miR-638 suppressed proliferation, migration, while promoted apoptosis in both wild U266 cells and circ-PTK2-overexpressed U266 cells; meanwhile, overexpressing miR-638 also suppressed MEK/ERK and WNT/β-catenin pathways in both wild U266 cells and circ-PTK2-overexpressed U266 cells. Knocking down miR-638 achieved opposite effect in both wild LP-1 cells and circ-PTK2-knocked-down LP-1 cells. In conclusion, circ-PTK2 promotes cell proliferation, migration, suppresses cell apoptosis via miR-638 mediated MEK&ERK and WNT&β-catenin signaling pathways in MM.